sistem informasi PENGEMBANGAN SISTEM INFORMASI SURVEILANS SARI PADA RESPONTIME PELAPORAN SARI DI RUMAH SAKIT UMUM Dr. SAIFUL ANWAR - Desma Legawa; Ratna Wardani; Ery Olivianto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Severe Acute Respiratory Infection (SARI) is an acute infectious disease that occurs in the respiratory tract and is better known as Pneumonia. The percentage of deaths in various countries caused by pneumonia has reached 30% and is in the age range of less than 5 years. In Indonesia, in the period from May 2013 to April 2015, there were 1,697 cases of the disease, while at Dr Saiful Anwar Hospital in 2022, 56 cases were caused by SARI with the influenza virus. The data collection process is done manually, resulting in delays in reporting problems. This study aims to analyze the effect of Web-Based SARI Information System Development on Sari Reporting Respontime at Dr. Hospital. Saiful Anwar (RSSA) which is useful for speeding up the process of reporting SARI surveillance from sentinels to the Ministry of Health. The design method uses a waterfall diagram which includes analysis, design, coding, and testing. The results of this study are web-based SARI applications where the Ministry of Health has not yet provided an application for data recapitulation processes for every sentinel in the territory of Indonesia, for this reason researchers innovate to create information-based systems web so that in reporting after using the web application the impact is more effective and efficient thus speeding up the reporting process.